A Comparative Analysis of Swasthya Sathi and West Bengal Health Scheme - Ahmed, Shahbaaz (Management Journal for Advanced Research, 2025)
The healthcare landscape in West Bengal has witnessed significant reforms with the introduction of Swasthya Sathi and the West Bengal Health Scheme (WBHS). Swasthya Sathi, a flagship health insurance scheme, provides coverage to families, while WBHS caters to government employees and their dependents. This comparative analysis delves into the key features, benefits, and limitations of both schemes, evaluating their impact on healthcare accessibility and quality in the state. The study examines the schemes' coverage, target population, services offered, implementation mechanisms, and financial implications, highlighting similarities and differences. Notably, Swasthya Sathi offers cashless treatment up to ₹5 lakhs per annum, whereas WBHS provides reimbursement-based benefits. Findings suggest that while both initiatives aim to provide financial protection and improved healthcare, there are notable variations in their scope, reach, and operational efficiency. The analysis provides insights into the strengths and weaknesses of each scheme, informing policymakers and stakeholders about potential areas for improvement and optimisation, and contributing to the discourse on healthcare reform in West Bengal.